2006
DOI: 10.1542/peds.2005-2925
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Various Tests for the Diagnosis ofHelicobacter pyloriin Egyptian Children

Abstract: The urea breath test and HpSTAR stool antigen kit are reliable tests for the noninvasive diagnosis of H. pylori among children living in the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 32 publications
7
61
1
3
Order By: Relevance
“…Low sensitivity among young children with antibody tests has also been reported, and it was believed to result from immaturity of the immune response and to be affected by transfer of maternal IgG antibodies to H. pylori [14] [20]. We found low sensitivity and specificity of UBT and low sensitivity of S-Ab in Group I with 1 to 6 years old patients as previously reported.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Low sensitivity among young children with antibody tests has also been reported, and it was believed to result from immaturity of the immune response and to be affected by transfer of maternal IgG antibodies to H. pylori [14] [20]. We found low sensitivity and specificity of UBT and low sensitivity of S-Ab in Group I with 1 to 6 years old patients as previously reported.…”
Section: Discussionsupporting
confidence: 81%
“…Because invasive tests can confirm H. pylori infection directly, they are recommended as more suitable tests for the detection of infection than non-invasive tests. However, feasible accuracy of non-invasive tests for the initial diagnosis has been presented in many reports [14]- [20]. Additionally, false results from invasive tests may occur due to patchy density of H. pylori, active bleeding in the stomach, or the presence of other pathogens producing urease in stomach such as non-Helicobacter pylori Helicobacters [21] [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also the outcome of a multicenter Japanese stu dy conducted in 2002, making UBT a reliable test for H. pylori infections [40] . Study from developing world also suggest that UBT is a highly accurate and reliable diagnostic modality as reflected by another study form Egypt that revealed a sensitivity and specificity of UBT to be 98% and 89% respectively [41] .…”
Section: Practical Application Of Carbon Breath Testingmentioning
confidence: 90%
“…In developing countries infants have high infection rate (up to 50%) as early as of 2 year old [6] and most of them harbor the organism [7] . H. pylori constitutes a real challenge in Egypt as its prevalence in children is noted to be high ranging from 33 -60% and up to 90 % in adults [8] .…”
Section: Introductionmentioning
confidence: 99%